PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VB SD NEGERI 136 PEKANBARU - Saspita, Putri; Alpusari, Mahmud; Zufriady, Zufriady (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrac: The reearch is based on the outcomes of student’s learning. This is because the teachers are not able to optimize the use of media in learning, they always use the lecture method and make students bored quickly. This study aims to apply the type of cooverative learning model make a match to increase the learning outcomes of the science students in Public Elementary School 136 class VB. This research is a classroom action reserch, the results of the study shoow that the science learning outcomes of the VB class students inceased after the cooperative learning model make a match was implemented. This is priven by the in cerease learning outomes, the results of the study obtained an average basic score of 63,61 increased in the cycle I by 13.75% to 72.36%. In the cycle II the average score of students also inceased by 26.20% to 800.28. On the basic score students classical mastery of science learning is 28.94% (incomplete). After applying the cooperative learning model type make a match in the cycle I the classical learning completenes of thhe students increased to 68.42% (incomplete), in the cycle II students classical learning completeness increased to 86.42% (complete).Key Words: Make a Match, Science Learning